The Effect of Education on Knowledge of Vitamin A Capsules in Cikondang Village, Cibeber District, Cianjur Regency, Indonesia - Hasni Rahmah; Soffa Abdillah; Natasya Putri Khaerani; Yani Suryani (Health Dynamics, 2025)
Background: Vitamin A is a critical nutrient that dissolves in fat, is stored in the liver, and must be sourced externally, as the body cannot produce it. Its significance for toddlers and children is undeniable, particularly in preventing infections and enhancing the body’s immunity. Methods: This study decisively examines the knowledge of mothers in Cikondang Village, Cibeber District, Cianjur, Indonesia, regarding the administration of vitamin A capsules to their toddlers. We employed an analytical report method to assess this important issue. A total of 20 mothers were sampled using a total sampling technique, and primary data was collected directly from the respondents with suitable instruments. Results: The results are compelling. Before counseling, 13 respondents (65%) were classified as having poor knowledge, with an average score of 53.05. Following the counseling session, 12 respondents (60%) demonstrated a significant improvement, moving into the good knowledge category, with an average score of 78.30. The Wilcoxon test analysis confirmed these findings with a p-value of 0.000. Conclusions: counseling has a profound and measurable impact on maternal knowledge. Local health services must continue to provide education on the critical importance of vitamin A consumption.